Modelling Energy Use in Agriculture: A Case Study in Bihar, India - Hurst, Christopher (Brighton, England: Institute of Development Studies, 1983)
This paper analyzes the feasibility of various sources of energy for low-lift irrigation on the northeast Indian plains. A linear programming model is developed to predict the general equilibrium state of the economy of Pulkahi. This model is used to predict the effects on agricultural production of various conventional and non-conventional technological endowments.
" DP 190 November 1983."
At head of title: Agriculture and rural problems.
Includes bibliographical references: p. 51.
ne 9/04/2018
Loans
Keywords: Agriculture